Multiobjective optimization for energy efficiency in cloud radio access networks - Sharma, S.; Yoon, W. (International Journal of Engineering Research and Technology, 2019)
In this paper our goal is to optimize the energy efficiency (EE) of massive multi-input multi-output (MU-MIMO) systems through Cloud Radio Access Network (C-RAN). First we obtain the maximum energy efficiency with four user association algorithms, named nearest-based user association (NBUA), full user association, multi-candidate RRHs user association (MCRUA), and improved (MCRUA), respectively. Then we consider a multiple-objective optimization approach (MOOP) which is non -convex. Pareto solution using weighted Tchebycheff method is proposed to convert MOOP into equivalent single-objective optimization problem (SOOP). The simulation results show comparisons of the four user association algorithms in which the improved MCRUA achieves higher performance.
Keywords: Energy efficiency; Multiobjective optimization; Pareto optimal